Vývoj aplikace pro generování dokumentace .NET knihoven - Akopyan, Denis; Pecinovský, Rudolf, 1954-; Suchan, Vladimír; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2022)
This thesis aims to research and develop a documentation-generating application for .NET libraries. The main objective was to create a tool for .NET developers that want to extract source code documentation and export it into their desired format while keeping the application extensible, cross-platform, and easy to use. The theoretical part of the thesis shall cover the development planning and the expected result of the project. The empirical part of the thesis illustrates the exact process of development. Designing a decoupled project structure had the most attention dedicated to it. The expected result of this thesis project is a working cross-platform and open-source application that can generate documentation from .NET libraries and is extensible via plugins.
Vedoucí práce: Rudolf Pecinovský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor bakal. práce]; bakalářské práce; bachelor's theses